The influence of flipbook learning media, learning interest, and learning motivation on learning outcomes - Bunari, Bunari; Setiawan, Johan; Ma’arif, Muhammad Anas; Purnamasari, Reski; Hadisaputra, Hadisaputra; Sudirman, Sudirman (Intelektual Pustaka Media Utama, 2024)
The aim of this research is to investigate the influence of flipbook learning media, learning interest, and learning motivation on junior high school students' learning outcomes. The method used is the regression method with a quantitative approach. This research was conducted at Junior High School 1 Yogyakarta with a sample of 64 class VIII social studies students. Data collection consists of interviews, observations, and documentation. Prerequisite test analysis consists of tests for normality, multicollinearity, and heteroscedasticity. Hypothesis testing using simple regression, and multiple regression. The research results show that there is an influence: i) flipbook learning media on learning outcomes with a tcount of 73.33, a significance value of 0.000 0.005, ii) interest in learning on learning outcomes with a tcount of 33.678, a significance value of 0.000 0.005, iii) learning motivation on learning outcomes with a tcount of 30.678, a significance value of 0.000 0.005, and iv) flipbook learning media, learning interest, and learning motivation together on learning outcomes with Fcount 47.879 Ftable 2.77 with a significance of 0.000 0.005. The conclusion is that the use of flipbook learning media, increasing interest in learning, and strengthening learning motivation can support each other to achieve optimal learning outcomes for students.